Reviewing China-AUKUS Tensions through Constructivism - Cahya Kalanuzza (Global Local Interactions: Journal of International Relations, 2023)
AUKUS is a relatively new trilateral pact. By aiming to maintain security and peace in the Indo-Pacific, AUKUS will indirectly deal with China as a country that is considered to have an important position in the region at this time. This research was conducted using a qualitative method whose sources were obtained from books, journals, scientific papers, etc. related to the problems between AUKUS and China. In this research, the tension between AUKUS and China will be discussed from the perspective of constructivism which assumes that the tension between the two comes from the perceptions that arise. This means that the tension that exists between AUKUS and China does not originate from material things as many neorealist or neoliberalist groups say. Rather, it is the different ideas/norms between the two camps that create tension. The AUKUS camp, which carries a democratic mission to maintain peace, is under a global hegemon that wants to maintain the current international structure, namely the United States. Where the United States secures the Indo-Pacific along with its two allied countries. Even though there has been much criticism, this trilateral pact continues because they both agreed to make China their enemy in terms of regional security.